2000
DOI: 10.1034/j.1600-0501.2000.011006595.x
|View full text |Cite
|
Sign up to set email alerts
|

Alternative to the median region of the palate for placement of an orthodontic implant

Abstract: Tooth-borne anchorage may be one of the greatest limitations of modern orthodontic treatment, because teeth move in response to forces. Previous investigators have placed temporary implants in the median-sagittal palate in order to establish maximum anchorage. This area, however, may be characterized by relatively low vertical bone support. The aim of this study was therefore to find an alternative palatal implant site which offers a higher amount of bone support. This study comprised 22 patients wishing for m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
111
1
19

Year Published

2001
2001
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 144 publications
(137 citation statements)
references
References 16 publications
6
111
1
19
Order By: Relevance
“…20,21,30,31 Anatomical features of the incisive canal have been studied in connection with rehabilitation of the maxillary anterior region [18][19][20][21][22][23][24] and the placement of orthodontic mini-implants. 30,[32][33][34] However, the consequences or the possibilities of incisor roots being in contact with the incisive canal following tooth movement are poorly documented in the orthodontic literature. Similar to the example presented in Figure 1, it was recently noted through 3D evaluation that the maxillary central incisor root in direct contact with the incisive canal following anterior retraction was associated with severe root resorption, but without any neurologic symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…20,21,30,31 Anatomical features of the incisive canal have been studied in connection with rehabilitation of the maxillary anterior region [18][19][20][21][22][23][24] and the placement of orthodontic mini-implants. 30,[32][33][34] However, the consequences or the possibilities of incisor roots being in contact with the incisive canal following tooth movement are poorly documented in the orthodontic literature. Similar to the example presented in Figure 1, it was recently noted through 3D evaluation that the maxillary central incisor root in direct contact with the incisive canal following anterior retraction was associated with severe root resorption, but without any neurologic symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…5,6 It has also been reported that a suitable bone thickness of the palate for miniimplants should be greater than 4 mm. 7 The success of mini-implants has been commonly reported to range between 70% and 89%. For miniimplants placed in the palate, however, success rates near 100% have been reported, although the comparison of different studies had its limitations.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have assessed bone quantity in the palate, but only a few have examined palatal bone densities. [5][6][7]11 Therefore, the purpose of this study was to quantitatively evaluate bone density in the palate so as to provide guidelines for mini-implant placement that are essential for implant site selection and implant success prediction.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To solve this problem, alternative implant sites have been used such as the retromolar 4,8) and ramus regions 6,9) in the mandible and the mid-palatal area 3,5,10) in the maxilla. Bernhart et al 1) stated that the median-sagittal region of the hard palate as a suitable location for implant placement is surgically very well accessible and offers a higher amount of bone support and excellent peri-implant conditions due to the attached mucosa. In Japan, however, there have been few reports on orthodontic treat- ment using a palatal implant for maximum anchorage.…”
Section: Discussionmentioning
confidence: 99%